Extracellular signals regulate the biogenesis of extracellular vesicles - Jin, Yong; Ma, Lele; Zhang, Wanying; Yang, Wen; Feng, Qiyu; Wang, Hongyang (Biological research, 2022)
Extracellular vesicles (EVs) are naturally released membrane vesicles that act as carriers of proteins and RNAs for intercellular communication. With various biomolecules and specific ligands, EV has represented a novel form of information transfer, which possesses extremely outstanding efficiency and specificity compared to the classical signal transduction. In addition, EV has extended the concept of signal transduction to intercellular aspect by working as the collection of extracellular information. Therefore, the functions of EVs have been extensively characterized and EVs exhibit an exciting prospect for clinical applications. However, the biogenesis of EVs and, in particular, the regulation of this process by extracellular signals, which are essential to conduct further studies and support optimal utility, remain unclear. Here, we review the current understanding of the biogenesis of EVs, focus on the regulation of this process by extracellular signals and discuss their therapeutic value.